Homelessness and the Institutional Ecosystem: Accessibility and Adequacy of Socioeconomic Support Services - Burak Acar (İstanbul Üniversitesi Sosyoloji Dergisi)
This research aims to examine the interactions of individuals experiencing homelessness with corporate service networks and service providers. The study aims to assess the extent to which the existing ecosystem of services meets the needs of homeless individuals and the accessibility and effectiveness of these services from the point of view of direct beneficiaries. In this research, a phenomenological approach from qualitative research methods was adopted to examine in depth the subjective experiences and perceptions of individuals experiencing homelessness. As a data collection tool, a semi-structured interview form developed in accordance with the research questions was used. 13 of the homeless individuals were included in the study, where in-depth face-to-face interviews were conducted with individuals using the snowball sampling technique. The data obtained have been brought together under 4 themes by using the descriptive analysis method: The diversity of corporate services for homeless individuals, the adequacy of corporate services, the attitudes and behaviours of service providers and the expectations of homeless individuals from corporate services. Homeless individuals; he meets his daily needs such as food, housing, and clothes mostly through non-governmental organisations. Sustainable and qualified services in the public sphere remain limited. public and local governments often offer short-term solutions to homelessness, such as housing limited to the winter season and a small amount of temporary cash support. One of the main problems of the homeless people’s access to social assistance and services is their lack of residence. A significant part of the participants highlighted their expectations at the point of providing permanent housing and permanent employment services instead of temporary and limited services at the point of solving the homelessness problem. As a result, it reveals that homeless individuals are largely dependent on non-governmental organisations to meet their basic needs, while public services offer inadequate and temporary solutions. Priority policy objectives should be set to provide long-term and sustainable solutions to the problem of homelessness.